Kyoto II and 'Houston Protocol': On the future of international climate policy - Udo E. Simonis (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2007)
The “Kyoto Protocol”, as the first and only implementation mechanism under the UN Framework Convention on Climate Change (UNFCCC), will expire by the year 2012. There are, however, many good reasons not to abandon this multilateral approach to climate change, but to soon go for a new round – “Kyoto II”. In doing so, the treaty must be thoroughly scrutinized for its deficiencies, as regards targets, instruments, and institutions. Particularly, and for various reasons, the Kyoto Protocol which is predominantly an economic concept should be supplemented by a technological companion - the “Houston Protocol” - under the UN Climate Convention. This paper shows how such an innovative “double strategy” of future climate policy might look like.
Keywords: 300; Klimaschutz; Klimaveränderung; Umweltabkommen; Internationale Umweltpolitik; Welt